The School of Antioch - Hovhanessian, Vahan S. (Peter Lang Inc., 2016)
The School of Antioch: Biblical Theology and the Church in Syria contains the latest conclusions and findings of academic research by specialized biblical scholars in biblical theology of the Church in the East commonly referred to as the School of Antioch. This collection of essays will be of special interest to scholars of theology and religion, including those interested in the fields of hermeneutics, Apocrypha, Chrysostom, Orthodox Eastern Christianity, and Eastern Christianity.
10.3726/978-1-4539-1550-9
Keywords: Johannes; Theodoretus; Theodorus; Antiochenische Schule; Theologie; Hermeneutik; Exegese